The vigilantes [compact disc, unabridged] - Griffin, W. E. B. (Griffin, W. E. B. Badge of honor, 2010)
There's a sudden spike in murders in Philadelphia, but no one seems to mind much because the victims are all lowlifes. However, when vigilante groups spring up claiming credit for some of the murders, Homicide Sergeant Matthew Payne hopes it isn't true. As the targets get bigger and events start moving out of control, Payne realizes that if he and his colleagues can't figure out who's behind this very soon, the violence could overtake them all.